Reliability and Variability of Lower Limb Muscle Activation as Indicators of Familiarity to Submaximal Eccentric Cycling - Walsh, Joel A.; McAndrew, Darryl J.; Shemmell, Jonathan; Stapley, Paul J. (Frontiers in Physiology, 2022)
Submaximal eccentric (ECC) cycling exercise is commonly used in research studies. No previous study has specified the required time naïve participants take to familiarize with submaximal ECC cycling. Therefore, we designed this study to determine whether critical indicators of cycling reliability and variability stabilize during 15 minutes of submaximal, semi-recumbent ECC cycling (ECC cycling). Twenty-two participants, aged between 18-51 years, volunteered to complete a single experimental session. Each participant completed three peak ECC torque protocol (PETP) tests, nine countermovement jumps and 15 minutes of submaximal (i.e., 10% peak power output produced during the PETP tests) ECC cycling. Muscle activation patterns were recorded from six muscles (rectus femoris, RF; vastus lateralis, VL; vastus medialis, VM; soleus, SOL; medial gastrocnemius, GM; tibialis anterior, TA), during prescribed-intensity ECC cycling, using electromyography (EMG). Minute-to-minute changes in the reliability and variability of EMG patterns were examined using intra-class correlation coefficient (ICC) and variance ratios (VR). Differences between target and actual power output were also used as an indicator of familiarization. Activation patterns for 4/6 muscles (RF, VL, VM and GM) became more consistent over the session, the RF, VL and VM increasing from moderate (ICC = 0.5-0.75) to good (ICC = 0.75-0.9) reliability by the 11th minute of cycling and the GM good reliability from the 1st minute (ICC = 0.79, ICC range = 0.70-0.88). Low variability (VR≤0.40) was maintained for VL, VM and GM from the 8th, 8th and 1st minutes, respectively. We also observed a significant decrease in the difference between actual and target power output (𝜒214 = 30.895, p = 0.006, W = 0.105), expressed primarily between the 2nd and 3rd minute of cycling (Z = -2.677, p = 0.007). Indicators of familiarization during ECC cycling, including deviations from target power output levels and the reliability and variability of muscle activation patterns stabilized within 15 minutes of cycling. Based upon this data, it would be reasonable for future studies to allocate ~15 minutes to familiarize naïve participants with a submaximal ECC cycling protocol.